Prevalence of acute kidney injury and sepsis in a Malaysian intensive care setting - Md Ralib, Azrina; Nanyan, Suhaila; Ramly, Nur Fariza; Mat Nor, Mohd Basri (Elsevier BV, 2017)
Introduction Acute Kidney Injury (AKI) is common in patients admitted to the intensive care unit, occurring in 30 to 60% of patients. The high incidence of AKI in our population may be attributed to sepsis. Sepsis is the leading cause of ICU admission. The Malaysian Registry of Intensive Care (MRIC), an annual ICU audit performed in all Malaysian ICUs. This registry serves as an excellent avenue to explore the incidence of septic AKI in our local ICU.